Preservative-free IOP-lowering medications: potential advantages - I.B. Alekseev; I.A. Koroleva (РМЖ "Клиническая офтальмология")
I.B. Alekseev1, I.A. Koroleva2 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2City Clinical Hospital No. 15, Moscow, Russian Federation According to the World Health Organization, glaucoma is the second leading cause of blindness in the world. Pharmacotherapy for glaucoma implies long-term instillations of IOP-lowering drugs. However, more glaucoma medications per day are required with time. In these cases, fixed-dose combinations containing several active ingredients are beneficial. Potential advantages of fixed-dose combinations include reduced costs, lower risk of washout, less instillations, reduced medication regimen complexity, and saved time. This results in better treatment compliance. Reduced preservative exposure is important as well. Many studies have demonstrated that preservatives induce local adverse reactions. Elimination or minimization of adverse reactions accompanying long-term glaucoma therapy is an important resource to improve treatment compliance and, therefore, to prevent vision loss and to maintain the quality of life. Hence, glaucoma patients may benefit from the avoidance of the addit ional risk of ocular surface disorders resulting from preservative exposure. Keywords: glaucoma, intraocular pressure, monotherapy, combined treatment, fixed-dose combinations, prostaglandin analogues, ocular surface, compliance, tafluprost, Tapticom. For citation: Alekseev I.B., Koroleva I.A. Preservative-free IOP-lowering medications: potential advantages. Russian Journal of Clinical Ophthalmology. 2019;19(3):137–142. About the authors: 1Igor B. Alekseev — MD, PhD, Professor, ORCID iD 0000-0002-4506-4986; 2Irina A. Koroleva — MD, PhD, ophthalmologist, ORCID iD 0000-0003-1679-5701. 1Russian Medical Academy of Continuous Professional Education. 2/1, Barrikadnaya str., Moscow, 125993, Russian Federation. 2City Clinical Hospital No. 15. 23, Veshnyakovskaya str., Moscow, 111539, Russian Federation. Contact information: Irina A. Koroleva, e-mail: tvoya-z@ya.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 24.06.2019.